An experimental comparison study between four different designs of solar stills - Hasanen M. Hussen; M.M. Younes; Wissam H. Alawee; A.S. Abdullah; Suha A. Mohammed; T.E.M. Atteya; Faheem Abbas; Z.M. Omara (Case Studies in Thermal Engineering, 2023)
In this experimental work, four different solar stills (SSs) have been tested. The SS systems are conventional SS (CSS), Double Slope SS (DSSS), Pyramid SS (PSS) and Tubular SS (TSS). Finding out which design will perform better at the testing site is the main objective. To minimize the shadow effect inside the DSSS and PSS the water basin has been elevated and the performance have been compared with the CSS. Additionally, phase change material mixed with Ag Nano particles has been employed with TSS, elevated basin DSSS and elevated basin PSS. The results indicated that, the productivity rise/thermal efficiency for DSSS, PSS and TSS are 28.5%/38.2%, 66%/43.7% and 96.5%/48.2%, respectively. But in case of DSSS and PSS with elevated basin the productivity rise/thermal efficiency showed 40.5%/40% and 84.5%/46.4%, respectively. Finally, the productivity rise/thermal efficiency for PSS with elevated basin and PCM showed the highest values of 116.4%/51.3%. The productivity for TSS is superior to those for the tested solar stills. In contrast to PSS, the TSS's manufacturing is more complicated and costly. Also, environmental and economic analyses have been considered, the achieved costs of the distilled freshwater were 0.024 and 0.019 $/L for the CSS and PSS (elevated basin and PCM), respectively. The environmental parameter of elevated basin PSS with PCM-Ag and CSS was 14.7- and 6.67-tons CO2 per year, respectively.